Prime Minister Decree No. 873 of the Year 2016 On Organizing the Ministry of Public Business Sector = قرار رئيس مجلس الوزراء رقم 873 لسنة 2016 بشأن تنظيم وزارة قطاع الأعمال العام - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic